Microbial activity and quality changes during decomposition of Quercus ilex leaf litter in three Mediterranean woods - Papa, S; Pellegrino, a; Fioretto, a (Applied Soil Ecology, 2008)
Changes in enzyme activities during litter decomposition provide diagnostic information on the dynamics of decay and functional microbial succession. Here we report a comparative study of enzyme activities involved in the breakdown of major plant components and of other key parameters (microbial respiration, fungal biomass, N, lignin and cellulose contents) in homogeneous leaf litter of Quercus ilex L. incubated in three evergreen oak woods in Southern Italy (Campania), differing for chemical and physical soil characteristics and microclimatic conditions. The results showed that the litter mass loss rates were similar in the three wood sites. Independently of the incubation sites, cellulase, xylanase and peroxydase activities showed seasonal variations with maximum and minimum levels in wet and dry periods, respectively, and this pattern closely matched microbial respiration. Activities of a- and b-amylase, instead, were high at the beginning of incubation and quickly decreased with decomposition progress because their substrate was rapidly depleted. Laccase activity, in contrast, was low at the beginning of incubation but after 6 months it increased signiﬁcantly. The increase of laccase activity was correlated to an increase in fungal biomass, probably reﬂecting a major shift in the litter microbial community. As concerns quality changes, N and lignin content did not signiﬁcantly change during decay. The cellulosic component started being degraded after about 6 months in the litter incubated in two of the three wood sites and from the start of decomposition in the third site. Apart from minor differences in the levels of certain enzyme activities, the data showed that the functional microbial succession involved in the decomposition of Q. ilex leaf litter did not change appreciably in response to differences in soil and microclimatic conditions in the incubation sites.
Keywords: Cellulose; Enzyme activities; Fungal biomass; Lignin; litter decomposition; Microbial respiration

Decomposition dynamics of Myrtus communis and Quercus ilex leaf litter: Mass loss, microbial activity and quality change - Fioretto, a; Papa, S; Pellegrino, a; Fuggi, A (Applied Soil Ecology, 2007)
The patterns of microbial respiration and enzyme activity (cellulase, xylanase, laccase and peroxidase) in the leaf litter of two evergreen sclerophyll species, Myrtus communis and Quercus ilex, were compared during decay in a low shrubland and in a coppice wood in a Natural Reserve in the Mediterranean area. The two litter types had similar initial amounts of lignin, cellulose and acid-detergentsoluble substances, but the litter from M. communis had a lower N content and higher C/N ratio. In spite of this, the decomposition rate of M. communis litter was higher than for Q. ilex. Whilst no seasonal variation was observed in the rate of organic matter degradation, respiration and extractable cellulase and xylanase activities showed seasonal variation in both litter types with the highest values in winter–early spring and the lowest in summer, and showed positive correlations with water content. Peroxidase activity exhibited a seasonal pattern and was higher in Q. ilex than in M. communis, while laccase activity was higher in M. communis and increased with fungal biomass as degradation progressed. Nevertheless, no relationship was found between laccase and peroxidase activity and lignin degradation. The results obtained indicate that the seasonal alternation of moist and dry periods is the major factor inﬂuencing soil biological activity in the Mediterranean area. The occurrence of pronounced seasonal variation in litter enzyme activity prevents the determination of possible correlations with litter mass loss.
Keywords: Cellulose; Enzyme activity; Fungal biomass; Lignin; litter decomposition; Microbial respiration